A proinflammatory stem cell niche drives myelofibrosis through a targetable galectin-1 axis - Li, R; Colombo, M; Wang, G; Rodriguez-Romera, A; Benlabiod, C; Jooss, NJ; O'Sullivan, J; Brierley, CK; Clark, S-A; Pérez Sáez, JM; Fernández, PA; Schoof, EM; et al. (American Association for the Advancement of Science, 2024)
Myeloproliferative neoplasms are stem cell-driven cancers associated with a large burden of morbidity and mortality. Most patients present with early-stage disease, but a substantial proportion progress to myelofibrosis or secondary leukemia, advanced cancers with a poor prognosis and high symptom burden. Currently, it remains difficult to predict progression, and therapies that reliably prevent or reverse fibrosis are lacking. A major bottleneck to the discovery of disease-modifying therapies has been an incomplete understanding of the interplay between perturbed cellular and molecular states. Several cell types have individually been implicated, but a comprehensive analysis of myelofibrotic bone marrow is lacking. We therefore mapped the cross-talk between bone marrow cell types in myelofibrotic bone marrow. We found that inflammation and fibrosis are orchestrated by a "quartet" of immune and stromal cell lineages, with basophils and mast cells creating a TNF signaling hub, communicating with megakaryocytes, mesenchymal stromal cells, and proinflammatory fibroblasts. We identified the β-galactoside-binding protein galectin-1 as a biomarker of progression to myelofibrosis and poor survival in multiple patient cohorts and as a promising therapeutic target, with reduced myeloproliferation and fibrosis in vitro and in vivo and improved survival after galectin-1 inhibition. In human bone marrow organoids, TNF increased galectin-1 expression, suggesting a feedback loop wherein the proinflammatory myeloproliferative neoplasm clone creates a self-reinforcing niche, fueling progression to advanced disease. This study provides a resource for studying hematopoietic cell-niche interactions, with relevance for cancer-associated inflammation and disorders of tissue fibrosis.